EVALUASI PASCA HUNI PERFORMANSI FISIK INSTALASI KEBIDANAN DAN PENYAKIT KANDUNGAN RUMAH SAKIT PKU MUHAMMADIYAH GAMPING - Siti Hardiyanti Adam; Widodo Hariyono; Iswanta Iswanta (Universitas Muhammadiyah Yogyakarta, 2016)
Hospitals must meet the facilities and infrastructure technical requirements of the hospital that support health care services completely. The evaluation of Hospital buildings standard's fulfillment can be done by Post Occupancy Evaluation. The study used mix method. Population consisted of all internal user in Obstaetric and Gynaecology Unit. There are 23 samples that determined by shovin formula. The result of study showed that location of Obstetrics and Gynecology Unit is not easy to be reached from Emergency Room, Intensive Care Unit, and Operating Room. Location, room availability, width, lighting, humidity, and temperature in Obstetrics and Gynecology Unit are not fulfill the standard yet. Technical and functional aspects are appropriate with Depkes 2007, process aspect is almost appropriate with Depkes 2007.